Elemental and nutritional analysis of Punica granatum from Turkey - (:unkn) unknown (MARY ANN LIEBERT INC, 2007)
Twenty different varieties of pomegranate (Punica granatum) from Turkey were analyzed for vitamin C level, lipid content, sterol determination, anthocyanin content, and elemental analysis (Ca, Mg, P, Fe, Na, and K studies). Vitamin C content range of 1,050-312 mg/100 g, oil content range of 2.41-3.73%, sterol content range of 5.78-8.43%, anthocyanin content range of 2,100-4,400 mg/L, potassium range of 250-1,200 ppm, calcium range of 35-326 ppm, magnesium range of 176-427 ppm, iron range of 21-46 ppm, sodium range of 35-76 ppm, and phosphorus range of 12-43 ppm were observed in these varieties.
Keywords: anthocyanin; minerals; oil content; phytosterol; Punica granatum; vitamin C; ORGANIC-ACIDS